Multilab EcoFAB study shows highly reproducible physiology and depletion of soil metabolites by a model grass. Issue 2 (24th January 2019) - Sasse, Joelle; Kant, Josefine; Cole, Benjamin J.; Klein, Andrew P.; Arsova, Borjana; Schlaepfer, Pascal; Gao, Jian; Lewald, Kyle; Zhalnina, Kateryna; Kosina, Suzanne; Bowen, Benjamin P.; Treen, Daniel; et al.
Summary: There is a dynamic reciprocity between plants and their environment: soil physiochemical properties influence plant morphology and metabolism, and root morphology and exudates shape the environment surrounding roots. Here, we investigate the reproducibility of plant trait changes in response to three growth environments. We utilized fabricated ecosystem (EcoFAB) devices to grow the model grass Brachypodium distachyon in three distinct media across four laboratories: phosphate‐sufficient and ‐deficient mineral media allowed assessment of the effects of phosphate starvation, and a complex, sterile soil extract represented a more natural environment with yet uncharacterized effects on plant growth and metabolism. Tissue weight and phosphate content, total root length, and root tissue and exudate metabolic profiles were consistent across laboratories and distinct between experimental treatments. Plants grown in soil extract were morphologically and metabolically distinct, with root hairs four times longer than with other growth conditions. Further, plants depleted half of the metabolites investigated from the soil extract. To interact with their environment, plants not only adapt morphology and release complex metabolite mixtures, but also selectively deplete a range of soil‐derived metabolites. The EcoFABs utilized here generated high interlaboratory reproducibility, demonstrating their value in standardized investigations of plant traits.